Evolutionary unraveling: new insights into the Persicaria amphibia complex - Ballestas, Gabriella; Nobles, Alexander; Hwang, Yoojeong; Kwak, Myounghai; Yoo, Mi-Jeong (Frontiers in Plant Science, 2024)
The Persicaria amphibia complex exhibits significant morphological variation depending on its habitat, existing in either aquatic or terrestrial forms. Traditionally, four distinct elements have been recognized based on morphological features along with their distinct geographical distributions. Recent studies suggest that the Asian element may be genetically distinct from the European and American elements. However, a comprehensive study on the genetic differentiation among all four elements remains lacking. This study aimed to leverage whole plastid genome sequences and ITS2 haplotypes to comprehensively assess the genomic diversity within the Persicaria P. amphibia complex. Notably, we included multiple individuals from New York State to resolve the ongoing debate regarding the taxonomic status of two American elementswhether they represent a single species or distinct entities. Our analysis revealed a well-supported monophyletic clade encompassing all four elements, endorsing their own section, Amphibia. . Notably, the terrestrial form of the American element is sister to all other elements, suggesting it deserves its own species status. This reinstates its historical name, P. coccinea, separating it from the broader P. amphibia. Furthermore, distinct compositions of the ITS2 haplotypes differentiated the four elements, although the European element should be further investigated with more sampling. The most intriguing discovery is the identification of putative hybrids between the two American elements. In one population out of four putative hybrid populations, all three entitiesthe two parent species and their hybrid offspringthrive together, showcasing a fascinating microcosm of ongoing evolutionary processes. This study opens new avenues for exploration. Unraveling the intricate genetic tapestry within each American species and their hybrid populations remains a compelling next step. By delving deeper into their genetic makeup, we can gain a richer understanding of their evolutionary trajectories and the intricacies of their interactions. Finally, it is estimated that the two species of sect. Amphibia diverged approximately 4.02 million years ago during the Pliocene epoch, when there was a significant global cooling and drying trend.